A quick comparison model on optimizing the efficiency of photovoltaic panels in collecting solar radiation - Yihe Bao; Haohe Bao (Scientific Reports, 2024)
Abstract Few scholars study light efficiency of solar-cell arrays in theory, while it is difficult to experimentally determine the maximum capacity of a photovoltaic panel to collect solar radiation. This paper proposes a solar energy comparison model (SECM), considering the sunshine duration changes every day to optimize the solar radiation collection model in an ideal state for a whole year, which is easy to use, and can quickly obtain the optimal tilt angle of photovoltaic panels and the solar radiation collecting efficiency enhancement of intelligent light tracking photovoltaic panels. The results show that the sunshine duration is an important factor affecting the solar radiation received by photovoltaic panels. In regions from 66°34′N to 66°34′S, intelligent light tracking photovoltaic panels can increase the collected solar radiation by at least 63.55%, up to 122.51% compared to stationary photovoltaic panels during the effective light time, which is much higher than what most people generally thought. And the advantage of intelligent light tracking photovoltaic panels is more obvious in high latitudes, with a longer and more variable sunshine duration. These findings provide a theoretical basis for the solar radiation collection and photovoltaic panels.